2019
DOI: 10.1017/s1431927619008675
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Formation Mechanisms of δ-Hydrides in Variable Grain Size Zircaloy-4 Studied by Electron Backscatter Diffraction

Abstract: Microstructure and crystallography of δ phase hydrides in as-received fine grain and 'blocky alpha' large grain Zircaloy-4 (average grain size ~11 µm and >200 µm, respectively) were examined using electron backscatter diffraction. Results suggest that the matrix-hydride orientation relationship is {0001} ||{111} ; < 112 ̅ 0 > || < 110 > for all the cases studied. The habit plane of intragranular hydrides and some intergranular hydrides has been found to be {101 ̅ 7} of the surrounding matrix. The morphology of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…The presence of stacking faults could be explained by a strain accumulation, originating from the lattice mismatch between the forming hydride and α-Zr matrix. Wang et al [36] previously showed that α-Zr grains within such hydride pockets exhibit a difference in orientation compared to the parent grain. Therefore, further growth of the hydride can be attributed to a large strain induced deformation, which causes stacking faults to propagate from the interface into the matrix.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of stacking faults could be explained by a strain accumulation, originating from the lattice mismatch between the forming hydride and α-Zr matrix. Wang et al [36] previously showed that α-Zr grains within such hydride pockets exhibit a difference in orientation compared to the parent grain. Therefore, further growth of the hydride can be attributed to a large strain induced deformation, which causes stacking faults to propagate from the interface into the matrix.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above and by Wang et al, there are two types of grain boundary hydrides [18], classified based on their growth parallel or normal to the boundary and referred to respectively as a-type and btype. Note that the hydride studied in our preliminary work, ref.…”
Section: Hydride Growthmentioning
confidence: 99%
“…It has been recently reported that H/D charged Zircaloy-4 sample shows, two types of (>μm sized) intergranular hydrides, described in two distinct type if the hydride is along (a-type) or perpendicular (btype) to the grain boundary, that appear to be different to those growing at twin boundaries (for more details see ref [18]). At the length scale seen in the SEM or during FIB preparation, please note that what we tend to refer to as a hydride is often actually an assembly of smaller hydrides, i.e.…”
Section: Microstructure In H/d Charged Blocky-α Zircaloy-4mentioning
confidence: 99%
See 1 more Smart Citation
“…Grain size effect on hydride precipitation in Zircaloy-4 plate has been studied by Wang et al. [9], more intergranular hydrides were found in the fine grain sample with higher density of preferential nucleation sites, that is, grain boundary (GB). The hydride precipitation at grain boundary can produce orientation gradients in the adjacent grain [9] resulting in the nucleation of cross-boundary hydride via an auto-catalytic mechanism [10,11] which related to the collective shear on the slip plane in both grains and the grain boundary energy.…”
Section: Introductionmentioning
confidence: 99%